MENINGKATKAN KECERDASAN NATURALIS MELALUI PEMBELAJARAN SAINS - Rohenah Rohenah; Isti Rusdiyani; Laily Rosidah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2021)
Naturalist intelligence is the ability of a person to understand the natural surroundings, to recognize animals, plants, natural phenomena as well as to have sensitivity to the environment. Naturalist intelligence of group B of children in PAUD Al-Maidah Serang Banten is still low, this is due to a lack of stimulation and proper activities that can support the development of children’s naturalist intelligence so that they can develop optimally. So it takes interesting and fun activities for children, one of which is through learning science. This study aims to improve naturalist intelligence in group B children at PAUD Al-Maidah. The method used in this research is a classroom action research method designed in a repetitive cycle, in this study consisting of II cycles. In cycle I there were 8 actions and cycle II there were 4 actions, with success criteria reaching 75 %. The subjects in this study were at PAUD Al-Maidah Bandung-Serang with a total of 10 children aged 5-6 years consisting of 8 boys and 2 girls. Based on the results of this study it is known that 1) in the pre-action naturalist intelligence of children 28%, 2) after the child was given action in cycle I, naturalist intelligence increased by 46%, 3) in cycle II it was obtained by 82%. Thus the naturalist intelligence of children has increased and is at a very well developed stage. Based on the results of the data obtained, it can be concluded that science learning can improve the naturalist intelligence of group B children in PAUD Al-Maidah Bandung-Serang.